The fabrication of electric motorcycle trainers to eliminate automotive misconceptions - Ramdhani, Ramdhani; Sriyono, Sriyono; Munawar, Wahid (Jurnal Pendidikan Vokasi, 2024)
This study aims to develop and implement learning media in the form of electric motorbike trainers to improve students' understanding of electric vehicle technology. The research method used is research and development (R&D) with the Successive Approximation Model (SAM) approach, which is applied in the electric vehicle technology course curriculum in the Automotive Engineering Education study programme. The participants in this study were undergraduate students involved in the learning process using an electric motorbike trainer. The research instruments included observation, interviews, questionnaires, and practical assessment sheets. The results showed that the designed electric motorbike trainer can be used properly and is feasible to operate in the learning process if used in accordance with procedures. Based on the assessment of material experts and media experts, this learning media is considered feasible to implement in learning. A survey of 47 students showed that 63% of respondents strongly agreed that this electric motorbike trainer is an effective innovation in supporting learning. In conclusion, the development of this electric motorbike trainer not only enriches the learning experience but also has the potential to improve students' understanding of electric vehicle technology. This research contributes to providing innovative learning media that is relevant to today's technological needs and can be adopted more widely in various technical education institutions.